First record of the genus Baptista Distant, 1903 (Heteroptera: Veliidae) from China, with descriptions of two new species - Ye, Zhen; Polhemus, Dan A.; Bu, Wenjun (Zootaxa, 2014)
The genus Baptista Distant, 1903, is recorded for the first time from China. Four species are treated in this paper, with B. digitata Andersen, 1989 and B. hoedli Zettel, 2004 newly recorded from China and two additional species, B. curvicornis sp. n. and B. obtusa sp. n., described as new to science. Photographs of the male and female dorsal habitus, male fore legs, male abdominal sternites, and male genitalic structures are provided, accompanied by line drawings of the male fore tibial details, male paramere, habitat photographs, and a distribution map for all Baptista species. A key to all four species occurring in China is also provided to assist in future identification.